Formulation And Physical Evaluation Test Of Purple Potato (Ipomoea batatas L.Poir) Extract Gel Preparation As Natural Hair Dye - Deswita, Dwi; Dwiningrum, Riza; Pisacha, Iga Mayola; Suswidiantoro, Vicko (LPPM Universitas Dhyana Pura, 2025)
Hair dye is a cosmetic product used in hair care to restore the original color, cover the hair color, or create a new color. Purple tuber extract can be used as a natural dye because it contains anthocyanin pigments. This study aims to formulate and evaluate hair dye gel preparations from purple tuber extract in various concentrations, as well as to determine the optimum concentration to provide the best coloring results. Purple tuber extract is obtained through the maceration method. The gel is formulated in three variations of extract concentration, namely 5% (F1), 10% (F2), and 15% (F3), with a gel base. Evaluation of the preparation includes organoleptic tests, pH, homogeneity, viscosity, adhesion, spreadability, color stability test against sunlight and color stability test against washing. The results show that all formulas are stable and homogeneous. The pH is within the safe range for the scalp, namely pH 6. The viscosities are F1 = 8,600 cPs, F2 = 9,400 cPs, F3 = 10,100 cPs, respectively. The adhesive power of F1 = 1.83 seconds, F2 = 2.42 seconds, F3 = 3.01 seconds. The spread power of F1 = 6.5 cm, F2 = 5.3 cm, F3 = 4.7 cm. The coloring results show that F15% gives a brownish red color, F2 5% produces an even and intense purplish red color, and F3 10% is reddish purple. The F3 formula (10%) is the best formula because it produces the most optimal color, namely purplish red (Claret Violet) with stable physical characteristics.